Results of the GreenCleanS Project Funded by the Science Fund of the Republic of Serbia - Kolarski, Dejan; Lukic, Jelena; Vasovic, Valentina; Janković, Jelena; Mihajlovic, Draginja (Proceedings, Electrical engineering institute "Nikola Tesla", 2024)
The project funded by the Science Fund of the Republic of Serbia, Development of Green Technology to Mitigate Power Transformer Failures Induced by Elemental Sulphur and Change Current Hazardous Practice in Transformer Oil Regeneration, under the acronym GreenCleanS focuses on developing a new technology for removing elemental sulphur molecule (S₈) from mineral insulating oils used in power transformers (PT) utilization an innovative low-temperature desulfurization process. The technology development includes experimental work at the laboratory scale and pilot scale level (technology readiness level, TRL 4), as well as the demonstration of the technology in an operational environment, involving the treatment of 3 tons of oil in a mobile desulfurization unit to achieve TRL 7. The implementation of this innovative technology will contribute to reducing the number of transformer failures caused by mineral oils containing S₈, a highly corrosive compound.